CASASTROPIC; LAW ENFORCEMENT AGAINTS CORRUPTION IN INDONESIA - Firmansyah; Miftah Idris (UIN Palopo, 2025)
The purpose of this research is to provide solutions in law enforcement against corruption in Indonesia that occurs massively and damages the state order and by examining the aspects of law enforcement carried out to eradicate corruption crimes.This study uses a type of normative research with a conceptual approach. The collection method used is library research technique by identifying journals or writings related to corruption in Indonesia, integrating the theory of the L.W. Friedman legal system and the prophetic theory of kuntowijoyo to describe the chronic causes faced in law enforcement against corruption and find solutions in handling corruption in Indonesia. The results of the research, it can be seen from L.W. Friedman's approach to legal system theory; substance, structure and culture, where in this analysis the substance and structure are analyzed in an integrated manner by emphasizing the rules by focusing on the emergence of Law No. 19 of 2019 concerning the Corruption Eradication Commission related to the existence of the Corruption Eradication Commission and also the urgency of reverse proof in corruption cases and culturally refers to the problem of morality, where there are law enforcement personnel who are against the law themselves while in other contexts with offers solutions that highlight the prophetic theory of Kuntowijoyo by integrating it into the analysis in this paper which consists of; Transedental (ethical-spiritual values), humanization (humanizing human beings) that reject dehumanization or reject corruption is associated with deviations and abuse of power and liberation, namely liberating from pressure and intimidation, one of which is corruption. Keywords: Corruption, Law Enforcement, casastropic